A Narrative Review of Molecular, Immunohistochemical and In-Situ Techniques in Dermatopathology - J. A. Gabriel; N. Weerasinghe; P. Balachandran; R. Salih; G. E. Orchard (British Journal of Biomedical Science)
Skin disorders pose a significant health burden globally, affecting millions of individuals across diverse demographics. Advancements in molecular techniques have revolutionised our understanding of the underlying mechanisms of skin disorders, offering insights into their pathogenesis, diagnosis, and potential targeted treatment. Furthermore, the integration of molecular diagnostics into clinical practice has enhanced the accuracy of skin disorder diagnoses. Polymerase chain reaction (PCR), next-generation sequencing (NGS), and other molecular assays have allowed for the detection of infectious agents, assessment of genetic mutations, and profile gene expression patterns with unequalled precision. These techniques have proven instrumental in distinguishing between subtypes of skin cancers, aiding treatment strategies and prognostic assessments. Moreover, molecular profiling is increasingly guiding the selection of therapeutic agents, ensuring a personalised and effective approach to managing skin disorders. The application of PCR has revolutionised the field by enabling the identification of microbial DNA (i.e., Mycobacterium tuberculosis and Epstein-Barr Virus) in skin infections and detecting specific genetic mutations associated with dermatological disorders (e.g., BRAF). DNA sequencing technologies, such as next-generation sequencing, have facilitated the elucidation of genetic variations and mutations in skin diseases (i.e., bullous disorders), paving the way for personalised treatment approaches. Gene expression profiling techniques, such as microarrays and RNA sequencing, have provided insights into dysregulated pathways and molecular signatures associated with conditions ranging from inflammatory skin disorders to cutaneous malignancies. Immunohistochemistry and fluorescence in situ hybridization have proven invaluable in determining protein expression patterns and detecting chromosomal abnormalities, respectively, aiding in the characterization of skin lesions in conjunction with the molecular data. Proteomic studies have contributed to understanding the intricate protein networks involved in dermatological conditions (i.e., psoriasis), while epigenetic analyses have shed light on the role of epigenetic modifications in gene regulation within skin cancer (i.e., Malignant Melanoma). Together, these molecular techniques have laid the groundwork for targeted therapies and precision medicine in dermatology, with implications for improved diagnostics and treatment outcomes. This review focuses on the routinely employed molecular techniques within dermatopathology, with a focus on cutaneous malignancies, autoimmune diseases, infectious diseases, and neonatal screening which can be implemented in the diagnosis and contribute to improved patient care.